2019
DOI: 10.1016/j.ecoser.2019.100926
|View full text |Cite
|
Sign up to set email alerts
|

Nature commodification: ‘a necessary evil’? An analysis of the views of environmental professionals on ecosystem services-based approaches

Abstract: This is a repository copy of Nature commodification: 'a necessary evil'? An analysis of the views of environmental professionals on ecosystem services-based approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 69 publications
(114 reference statements)
0
20
0
Order By: Relevance
“…The monitoring of cultural services is particularly challenging to do at larger spatial scales because it excludes the use of specific common methods such as field survey. Despite environmental professionals seeing ES based approaches as being favourable (Martin-Ortega et al, 2019), to be able to inform managers of PAs, for example on the spatial pattern of different uses of the site, methods need to be feasible in terms of manpower and costs, coherent over time and cover a diversity of beneficiaries.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of cultural services is particularly challenging to do at larger spatial scales because it excludes the use of specific common methods such as field survey. Despite environmental professionals seeing ES based approaches as being favourable (Martin-Ortega et al, 2019), to be able to inform managers of PAs, for example on the spatial pattern of different uses of the site, methods need to be feasible in terms of manpower and costs, coherent over time and cover a diversity of beneficiaries.…”
Section: Introductionmentioning
confidence: 99%
“…Research on environmental governance (Hysing and Olsson, 2018) as well as on ES policy implementation (Saarikoski et al, 2018), have highlighted the importance of individuals actively championing new concepts and approaches within their organizations and sectors to facilitate change. Based on an interview study among policy practitioner identified as "frontrunners" in the implementation of ES in Sweden, the paper explores the functions and value of the concept in the practical implementation of biodiversity policies (similar designs have been used in e.g., Blicharska and Hilding-Rydevik, 2018;Keenan et al, 2019;Martin-Ortega et al, 2019). The study was carried out in the spring of 2020 and included 35 respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Crucial to successfully integrating and implementing ES are actors who actively promote the ES concept, facilitate communication between knowledge producers and users, and who foster new ideas within and between organizations (Saarikoski et al, 2018). It is therefore important to consider the uptake, interpretation, and translation of ES among such actors when discussing how the concept may change practices (Martin-Ortega et al, 2019). This section presents the results of an interview study with actors identified as "frontrunners" in the implementation of ES in Sweden, exploring their experiences with using the concept and illustrating critical challenges for policy practice.…”
Section: How Do Conceptual Innovations Matter For Practice?mentioning
confidence: 99%
“…Monetary and non-monetary measurement is one step in ensuring that values are recognised and, when appropriate, captured in decision making. Monetary values of ecosystems can be incorporated into decision-making through specific mechanisms such as incentives and price signals or via decision-making frameworks such as cost-benefit analysis or payments for ecosystem services (PES) schemes (Kumar, 2010;Martin-Ortega et al, 2019;Primmer et al, 2018). They have been criticised for converting nature into a tradable commodity, often associated with a process of privatisation (Gomez-Baggethun and Ruiz-Perez, 2011), thereby marginalising other frameworks for ecosystem conservation (Raymond et al, 2013).…”
Section: Metrics Of Value and Valuation Methodsmentioning
confidence: 99%